Association of increased telomere lengths in limited scleroderma, with a lack of age-related telomere erosion. Issue 12 (28th July 2008) - MacIntyre, A; Brouilette, S W; Lamb, K; Radhakrishnan, K; McGlynn, L; Chee, M M; Parkinson, E K; Freeman, D; Madhok, R; Shiels, P G
Abstract : Objectives: Telomere erosion, a feature of biological ageing, is implicated in a wide range of diseases. Its impact on autoimmune diseases remains unclear although autoantibodies against many telomere nucleoprotein components are prevalent in these diseases. We aimed to assess if telomere biology was abnormal in a cohort of patients with limited cutaneous systemic sclerosis (lcSSc). Methods: Telomere lengths in peripheral blood leucocytes (PBL) were determined using Southern blotting methods in a cohort of lcSSc subjects (n = 43; age range 37–80 years) and a control population (n = 107; age range 21–65 years). Results: Telomere lengths in lcSSc subjects were longer than controls (p<0.001), did not show age-related telomere erosion and differed significantly from age-matched controls only after 50 years of age (p<0.001). Conclusions: This is the first report of maintenance of telomere lengths in an autoimmune disease state. These data indicate aberrant telomere biology and irregular biological ageing from the fifth decade of life. These findings provide insight into compromised DNA damage repair in lcSSc. Whether these observations indicate a causal or consequential relationship requires further investigation. This in turn, may provide potential novel targets for therapeutic intervention.